A COMPREHENSIVE AYURVEDIC REVIEW ON LAVANGA (SYZYGIUM AROMATICUM) - Manish Pamnani*; Vinod Kumar; Kamini Kaushal; Mahesh Dixit (AYUSHDHARA, 2019)
Ayurveda means science of life. Ayurveda was from time immemorial and still it has its own importance in field of medical science. Ayurveda is divided into eight branches. Out of all these branches Dravyguna vijnana is one of them. It includes information about herbs which is described in ancient classical text of Ayurveda. In Ayurveda there is a saying if a Vaidhya has no proper knowledge regarding these herbs he is unable to provide proper treatment to patients. These herbs are backbone of Ayurveda. Among all herbs, Lavanga is a well known Ayurvedic herb. Lavanga are aromatic flower buds of a tree Latin named as Syzygium aromaticum which comes under myrtaceae family. It is known as Lavanga due to its Kapha lysing property. It posses other properties such as Deepana, Pachana, Ruchya, Chakshushya, Kapha-Pittaghana properties. It is used in Trishna, Chhardi, Aadhmana, Shoola, Kasa, Shwasa, Hikka, Kshaya named diseases.